From behind the bakery counter : exploring Cambodian women's transnational connections and sense of belonging - Andrew, Suzanne (Massey University, 2020)
This study foregrounds Khmer women’s stories of migration and settlement in New Zealand’s North Island towns. Specifically, it has engaged with women working in Khmer owned, New Zealand bakeries. Conceptually, a gender and migration lens was applied, supporting an understanding of the balancing act women encounter in their everyday lives, where bakery spaces simultaneously enable and disable Khmer women. Keeping this gender lens in mind, this study delved into Khmer women’s transnational social spaces and the ways in which they remain connected to their kin, culture and homeland. Focusing on the women’s everyday realities, the methodology used an ethnographic approach, to centre on the voices of Khmer women. This study identified that depending on their background, women’s personal migration journeys vary. This study concluded that belonging must be seen in a wider context than just about Khmer women identifying with either New Zealand or Cambodia as their homes. Women crafted their new life of belonging, where the memories of their families, friends, and former lives were constantly woven through their everyday activities and thoughts. A new, re-imagined existence was created, with women weighing their memories and knowledge of Cambodia’s realities, against the constraints and opportunities that bakeries offered. Significantly, Khmer women were placing family unity and their children’s welfare above their own happiness and aspirations, as they crafted this new kind of belonging.